PELESTARIAN FLORA DI LINGKUNGAN PURA TAMAN AYUN MENUNJANG ATRAKSI NOMINASI WARISAN BUDAYA DUNIA - Ni Nyoman Wirasiti; I Ketut Ginantra; A.A.G. Raka Dalem; I Ketut Muksin (Bumi Lestari Journal of Environment, 2011)
Taman Ayun is a tourist destination which is proposed as a world cultural heritage. Thus, the data about Taman Ayun are important things to be collected to support the proposal. This study is expected to provide data on flora. Data on flora were gathered based on site observation on September 5, 2008. The data collection was also supported by other data collecting techniques such as interview and literature review. Result of the study showed that there were 125 plant species around the temple. As much as 16,8 % were classified as rare/threatened or endangered, 1,6% rare and protected, and the rest (81,6 %) were not protected and not rare species. The highest proportion of the plant (30 %) were decorative plant. Others were material for ceremony (upakara) (21%), food and vegetables (19 %). All of those were covering 70 % of the plant. The rest were for medicine, providing shaded spots, animal fodder, other use and has not been used.